Risk factors for pregnancy induced hypertension. - Perera, N.A.N (My University, 2006)
A case control study which was carried out at Castle Street Hospital for Women during August 2006 to September 2006. 100 mothers having P.I.H. who were chosen as cases and 100 mothers with uncomplicated pregnancies who were chosen as controls. Experiencing two or more life events during pregnancy, mothers having a B.M.I. of 26kg/m2 or more before 16 weeks of P.O.A., mothers age 28 years or more, having a history of antepartum haemorrhage and standing for more than 1.5hrs at one stretch were risk factors for P .I.H.